A review of driving task factors / Nurfatin Atikah Mohd Sharudin - Mohd Sharudin, Nurfatin Atikah (2015)
The prevalence of accidents is increasing and road traffic injuries are expected to become the fifth leading factor of death by year 2030 if no plan is occupied. This review was done to summarise the basic concept of driving task and the factors affecting driving task. Besides, the performance models on driving safety on driving safety also being reviewed. Articles between the years 1960 till 2015 have been taken to be analysed in a narrative way. The definition of driving task itself needs to be understood among drivers in order to drive carefully. Besides, the human and environmental factors are important to determining safe driving task. Human factors include visual and psychological are mostly associated with the driving task. In addition, the performance models are listed based on the previous research, most of the models relate to driver's behaviour. Thus, this review can help the drivers understand the definition of driving task, how the factors affecting the driving task and performance models on driving safety. As a result, a safe driving performance can be achieved and the number of accidents will be reduced in future.